Predictors of discharge destination from acute care in patients with traumatic brain injury - Zarshenas, Sareh (BMJ Open, 2017)
INTRODUCTION: Many studies have assessed the predictors of morbidity/mortality of patients with traumatic brain injury (TBI) in acute care. However, with the increasing rate of survival after TBI, more attention has been given to discharge destinations from acute care as an important measure of clinical priorities. This study describes the design of a systematic review compiling and synthesising studies on the prognostic factors of discharge settings from acute care in patients with TBI. METHODS AND ANALYSIS: This systematic review will be conducted on peer-reviewed studies using seven databases including Medline/Medline in-Process, Embase, Cochrane Database of Systematic Reviews, Cochrane CENTRAL, PsycINFO, CINAHL and Supplemental PubMed. The reference list of selected articles and Google Scholar will also be reviewed to determine other relevant articles. This study will include all English language observational studies that focus on adult patients with TBI in acute care settings. The quality of articles will be assessed by the Quality in Prognostic Studies tool. ETHICS AND DISSEMINATION: The results of this review will provide evidence that may guide healthcare providers in making more informed and timely discharge decisions to the next level of care for patient with TBI. Also, this study will provide valuable information to address the gaps in knowledge for future research. TRIAL REGISTRATION NUMBER: Trial registration number (PROSPERO) is CRD42016033046.